A New Manganese Based-Metal Oxide Electrocatalyst Through Electrodeposition for Investigation of Effect on V(IV)/V(V) Side's Reversibility of All-Vanadium Redox Flow Batteries - Yalcin, Dilek; Gencten, Metin; Sahin, Yucel; Ozcan, Adnan (ELECTROCHEMICAL SOC INC, 2023)
Within the objective of this work, it is aimed to research, examine and bring to the literature as a new electrocatalyst material for enhancing the positive side's reaction of VRBs. To be able to achieve this goal, it has been synthesized a manganese-based electrocatalyst as MnO2 to enhance the reversibility reaction for the positive side of VRB and so, practical, feasible and reproducible pencil graphite electrode(PGE) has been chosen as a working electrode for the modification to be electrodeposited MnO2 onto it. It is characterized via X-ray methods to understand the structure and surface changings and electrochemical techniques to interpret electrochemical behavior and charge transfer resistance through cyclic voltammetry(CV) and electrochemical impedance spectroscopy(EIS). Within the scope of synthesizing, potential range, sulfuric acid and precursor concentration, and cycle number are optimized via CV and EIS. 0.5 M KMnO4 and 3.0 M H2SO4 medium with 50 cycle number within 50 mV s-1 scan rate in a -0.5/1.5 V potential range was decided to produce Mn-based metal-oxide as MnO2 electrocatalyst as optimum conditions. The original contribution of this study is that electrodepositing of manganese-based electrocatalyst as MnO2 on graphite based electrodes for redox flow battery in the literature.
Keywords: POSITIVE ELECTRODE; CYCLIC VOLTAMMETRY; GRAPHITE FELT; PRECIPITATION; NANOPARTICLES; Materials Science; Physics